Post-natal mortality of kids a pathoanatomical investigation - Manomohan C B (Department of Pathology, College of Veterinary and Animal Sciences, 1980)
A study was conducted to evaluate the pathoanatomical features of the important diseases causing mortality in kids. A total of 105 kids below six months were studied. Mortality was found to be highest in kids of the 0 - 3 month age group. Gastro – enteritis was found to be the most important cause of post – natal mortality in kids as this was the cause of death in 77 kids (73.3%). Gastritis was mainly manifested as a catarrhal type. Abomasal erosions, gastric ulcers and patchy necrotic abomasitis were also encountered in some cases. Enteritic lesions were seen in 72 cases of which 46 animals did not show any lesions in stomach. This included six cases of coccidiosis and one case of taeniasis. Enteritis was mainly manifested as catarrhal enteritis with infiltration of lymphocytes. Haemorrhagic enteritis and necrotic enteritis were seen in few cases. The mesenteric lymph nodes from some of these animals showed depletion of lymphocytes. Escherichis coli and Enterobacter aerogenes could be isolated from intestinal contents. The probable role of these organisms in the pathogenesis of the lesions has been discussed. Six kids had lesions of coccidial enteritis produced by Eimeria arloingi and Eimeria intricate. One animal died due to taeniasis caused by Moniezia sp. Pneumonia caused mortality in 18 kids (17.1%) 12 animals out of them belonged to 0 – 3 month age group. Lesions were mainly in the apical, cardiac and intermediate lobes. Basically the reaction was of suppurative lobes. Bronchitis, peribronchitis and necrosis were seen in some cases. Two cases showed interstitial fibrosis and one case showed infiltration of macrophages and giant cells. Streptococcus pneumonia and Klebsiella pneumonia were isolated from pneumonic lungs. Virulent Klebsiella pneumonia failed to produce pneumonia in kids when inoculated experimentally. The probability of kids possessing immunity against this organism and of multiple etiological factors has been discussed. In four cases toxic hepatitis was seen. The possible role of aflatoxin in the production of hepatitis has been discussed. In three animals renal cortical hypoplasia was noticed. One animal showed lesions of pox in tongue and corners of mouth. The animal at autopsy was found to have myocarditis, fibrinous pericarditis and necrotic glossitis. The death was considered to be due to these secondary complications. The present work has indicated the necessity for indepth study on the role of factors like immune status of the animals and co – pathogens in the causation of diseases in young kids.